Comparison of clinical outcomes of bilateral and unilateral unicompartmental knee arthroplasty for the treatment of knee osteoarthritis - Yu Hao; Jia Li; Jun Li; Feng Zhao; Xiaoguang Yu; Shunlong Liang; Chenda Zhang; Wei Dong; Guobin Liu (Scientific Reports)
Abstract The risks and benefits associated with simultaneous bilateral unicompartmental knee arthroplasty (UKA) continue to engender contentious debate. The aim of this study was to compare the clinical outcomes of simultaneous bilateral and unilateral UKA. A retrospective review was performed between 2019 and 2022 on 280 patients (130 simultaneous bilateral vs. 150 unilateral Oxford UKA) who performed by two experienced surgeons. Patients in both groups underwent surgery according to the Microplasty instrumentation system, with congruent postoperative management and carefully standardized follow-up. This study performed a comparative analysis between the two groups of patients with regard to postoperative laboratory tests, knee functionality, postoperative discomfort, and incidence of complications. There was a significant difference in the duration of disease between the two groups (U-UKA:6.05 vs. SB-UKA:7.80, P < 0.05). When it comes to laboratory examinations, a notable disparity emerged in hemoglobin levels, erythrocyte pressure volume, D-dimer concentrations, albumin levels, as well as indicators of inflammation among the two groups of patients (P < 0.05). There was a significant difference in operative time and blood loss between the two groups (P < 0.05), with no significant difference in complications. There was no significant difference in radiographic and prosthetic survival between the two groups (U-UKA: 99.3% vs. 98.5%). The HSS score, VAS, and ROM showed remarkable disparities between the two groups in the initial postoperative phase, albeit these distinctions gradually attenuated with the passage of time. Simultaneous bilateral UKA reduces the number of procedures without increasing the risk of surgical complications, but results in a markedly enhanced physiological response and a suboptimal perioperative experience. We strongly encourage the surgeon to work with the patient to determine a surgical strategy.